Amelioration of liver fibrosis with autologous macrophages induced by IL-34-based condition - Yuichi Igarashi; Haruka Wada; Masato Muto; Ryohei Sone; Yoshinori Hasegawa; Ken-ichiro Seino (Inflammation and Regeneration)
Abstract Background For the treatment of liver fibrosis, several novel cell therapies have been proposed. Autologous macrophage therapy has been reported as one of the promising treatments. So far, most studies have used colony-stimulating factor 1 (CSF-1) to induce the differentiation of macrophage progenitor cells. The receptor for CSF-1, CSF-1R possesses another ligand, interleukin 34. However, the therapeutic capacity for liver fibrosis by interleukin 34-induced macrophages has not been evaluated. Methods We have employed acute (bile duct ligation) and chronic (administration of carbon tetrachloride or thioacetamide) liver fibrosis models. Using these models, we evaluated the therapeutic capacity of macrophages induced by interleukin 34-based conditions. In most experiments, interleukin 4 was also added to the differentiation process to induce alternative-activated macrophages. As a mechanism analysis, we have examined liver inflammation and damage, the status of stellate cells, and the immunosuppressive capacity of the macrophages. Human macrophages were differentiated from CD14+ monocytes and analyzed. Results In both acute and chronic liver damage experiments, interleukin 34-induced macrophages significantly ameliorated liver fibrosis. The addition of interleukin 4 to the differentiation process resulted in an increase of obtained macrophages and a bias to alternative activated macrophages (so-called M2). The alternative activated macrophages (M2-type) showed a reproducible therapeutic effect of liver fibrosis with a suppression of parameters of liver inflammation and damage, stellate cells, and T cell activation. Similar macrophages could be differentiated from human CD14+ monocytes in the presence of interleukin 34 plus interleukin 4, and a therapeutic effect was observed using a humanized mouse model. Conclusions Interleukin 34-induced macrophages, particularly when additionally stimulated with interleukin 4, significantly ameliorated the liver fibrosis.